PURIFIKASI DAN PENCIRIAN ENZIM PROTEASE FIBRINOLITIK DARI EKSTRAK JAMUR MERANG (Makara Journal of Science, 2010)
Purification and Characterization of Fibrinolytic Proteases from Mushroom Volvariela volvaceae Extract. Edible straw mushroom (V. volvaceae) has been known used for improvement of blood circulation due to its fibrinolytic content. The objective of the study is to purify and characterize fibrinolytic protease from straw mushroom extract. Purification were performed through several steps, i.e. precipitation using ammonium sulphate 75%, dialyzed membran (cut-off 10 kDa), and ion-exchange chromatography using DEAE Sepharose. The active fraction of DEAE-Sepharose contains two purified protein bands with molecular weight of 12.9 and 15.8 kDa. The active fraction has specific activity of 0.383 U/mg with 2.7 fold higher purification compared to its crude extract. Both crude and purified enzymes had optimum activity at temperature of 50 ºC and pH 7 in 10 minutes of incubation. Fibrin zymographic profile demonstrated that the enzyme hydrolyzed fibrin, as well as casein, indicating their potent fibrinolytic activity. The enzyme was strongly inhibited by phenilmethylsulphonyl fluoride and N-p-tosil-L-lysinchloromethyl keton. This suggested that it was a serine protease. In summary, these results showed that crude and purified protease of straw mushroom (V. volvaceae) has fibrinolytic activities that can be applied for alternative thrombolytic therapy